Improve computational complexity of sobel edge detection using parallel contract anytime algorithm - Hossain, Md. Kamal; Ibtehaz, Md. Asif; Ashique, Md. Assaduzzaman (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016.